2020
DOI: 10.1080/14760584.2020.1758070
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles for preparation of antibodies and vaccines against infectious diseases

Abstract: Introduction: Vaccination remains very effective in stimulating protective immune responses against infections. An important task in antibody and vaccine preparation is to choose an optimal carrier that will ensure a high immune response. Particularly promising in this regard are nanoscale particle carriers. An antigen that is adsorbed or encapsulated by nanoparticles can be used as an adjuvant to optimize the immune response during vaccination. a very popular antigen carrier used for immunization and vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 134 publications
(115 reference statements)
0
67
0
Order By: Relevance
“…The GNPs can be designed in different shape and sizes such as nanospheres, nanorods, nanoshells (core and shell), and nanostars—which influences immune response (Dykman et al 2018 , Niikura et al 2013 ). Conjugation of GNPs with the antigens has been reported by several researcher for immunization studies against viral diseases such as Foot and mouth disease virus (Chen et al 2010 ), Influenza virus, West Nile fever virus and Hepatitis B virus (Dykman 2020 ). For Hepatitis E virus, use of gold fluorescent nanoclusters were reported earlier for tracking the dynamic behavior of vaccine in vivo and its immune response (Wang et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The GNPs can be designed in different shape and sizes such as nanospheres, nanorods, nanoshells (core and shell), and nanostars—which influences immune response (Dykman et al 2018 , Niikura et al 2013 ). Conjugation of GNPs with the antigens has been reported by several researcher for immunization studies against viral diseases such as Foot and mouth disease virus (Chen et al 2010 ), Influenza virus, West Nile fever virus and Hepatitis B virus (Dykman 2020 ). For Hepatitis E virus, use of gold fluorescent nanoclusters were reported earlier for tracking the dynamic behavior of vaccine in vivo and its immune response (Wang et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For the subsequent detection of these interactions, the enzyme-mediated growth or aggregation of Au-NPs is employed [ 6 ]. In the same way, components of viruses can be bound as antigens to gold nanoparticles to develop improved vaccination strategies [ 7 ]. Furthermore, surface modifications can be used, e.g., to create drug delivery systems when functionalized with therapeutics [ 8 , 9 , 10 , 11 ], as well as for photothermal therapy for cancer [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that gold nanoparticles are having significant vaccine adjuvant properties and the coated gold nanoparticles act by increasing inflammatory cytokines (TNF-α, IL-6, IL-12) production [ 25 ]. Gold nanoparticle complexes with transmissible gastroenteritis virus (TGEV) exhibited higher levels of IFN-γ, IL-1β and IL-6 in animals immunized with the complexes than those in animals challenged with only antigen [ 26 ].…”
Section: Metal Nanoparticles As Covid-19 Vaccine Adjuvantsmentioning
confidence: 99%